THE EFFECT OF METACOGNITIVE STRATEGY TRAINING AND RAISING EFL LEARNERS’ METACOGNITIVE KNOWLEDGE ON LISTENING PERFORMANCE - Khonamri, Fatemeh; Ahmadi, Faezeh (Indonesian Journal of Applied Linguistics, 2015)
This study investigated the effect of metacognitive strategy training and the degree of metacognitive knowledge on EFL learners’ listening comprehension achievement. To this end and to complement the results of previous research, the participants were also involved in a self-rating process through engaging in log writing and completing a performance checklist. The participants were 40 female intermediate students studying English in a language institute in the north of Iran. Paired and Independent sample t-tests were used to compare the performance of the experimental group to that of the control group. Students’ listening logs and performance checklists were also investigated for finding traces of raised awareness and increased strategy use.  Results proved that strategy training and students’ degree of metacognitive knowledge affected their listening achievement. The results were enlightening in that students indicated greater tendency to become more strategic learners as a result of the training they received. An analysis of participants’ self- rating corroborated the attained results.